New materials and their applications, 1987 : proceedings of the Institute of Physics conference, held at University of Warwick, 22-25 September 1987 - Burnay, S. G.; Institute of Physics (Great Britain) (Bristol ; Philadelphia : Institute of Physics)
Includes bibliographies and index.